Effect of Topography Degradation on Crater Size‐Frequency Distributions: Implications for Populations of Small Craters and Age Dating. Issue 20 (30th October 2017) - Xie, Minggang; Zhu, Meng‐Hua; Xiao, Zhiyong; Wu, Yunzhao; Xu, Aoao
Abstract: Whether or not background secondary craters dominate populations of small impact craters on terrestrial bodies is a half‐century controversy. It has been suggested that small craters on some planetary bodies are dominated by background secondary craters based partly on the steepened slope of crater size‐frequency distribution (CSFD) toward small diameters, such as the less than 1 km diameter crater population on the lunar mare. Here we show that topography degradation enlarges craters and increases CSFD slopes with time. When topography degradation is taken into account, for various‐aged crater populations, the observed steep CSFD at small diameters is uniformly consistent with an originally shallower CSFD, whose slope is undifferentiated from the CSFD slope estimated from near‐Earth objects and terrestrial bolides. The results show that the effect of topography degradation on CSFD is important in dating planetary surfaces, and the steepening of CSFD slopes is not necessarily caused by secondary cratering, but rather a natural consequence of topography degradation. Key Points: CSFD evolves with time due to the fact that topography degradation enlarges crater diameters Steep CSFD at lunar small crater diameters can be caused by topography degradation and does not necessarily require secondary craters Degradation is important in establishing the true production function and could cause crater density uncertainties up to 2.5 times